Evaluational adjectives. (5th September 2019) - Silk, Alex
Abstract: This paper demarcates a theoretically interesting class of evaluational adjectives . This class includes predicates expressing various kinds of normative and epistemic evaluation, such as predicates of personal taste, aesthetic adjectives, moral adjectives, and epistemic adjectives, among others. Evaluational adjectives are distinguished, empirically, in exhibiting phenomena such as discourse‐oriented use, felicitous embedding under the attitude verb 'find', and sorites‐susceptibility in the comparative form. A unified degree‐based semantics is developed: What distinguishes evaluational adjectives, semantically, is that they denote context‐dependent measure functions ( evaluational perspectives )—context‐dependent mappings to degrees of taste, beauty, probability, etc., depending on the adjective. This perspective‐sensitivity characterizing the class of evaluational adjectives cannot be assimilated to vagueness, sensitivity to an experiencer argument, or multidimensionality; and it cannot be demarcated in terms of pretheoretic notions of subjectivity, common in the literature. I propose that certain diagnostics for "subjective" expressions be analyzed instead in terms of a precisely specified kind of discourse‐oriented use of context‐sensitive language. I close by applying the account to 'find x PRED' ascriptions.